Therapeutic applications of mesenchymal stem cells for amyotrophic lateral sclerosis - Lewis, Christina M (BioMed Central, 2014)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease affecting the neuromuscular system and does not have a known singular cause. Genetic mutations, extracellular factors, non-neuronal support cells, and the immune system have all been shown to play varied roles in clinical and pathological disease progression. The therapeutic plasticity of mesenchymal stem cells (MSCs) may be well matched to this complex disease pathology, making MSCs strong candidates for cellular therapy in ALS. In this review, we summarize a variety of explored mechanisms by which MSCs play a role in ALS progression, including neuronal and non-neuronal cell replacement, trophic factor delivery, and modulation of the immune system. Currently relevant techniques for applying MSC therapy in ALS are discussed, focusing in particular on delivery route and cell source. We include examples from in vitro, preclinical, and clinical investigations to elucidate the remaining progress that must be made to understand and apply MSCs as a treatment for ALS.